O desejo como fundador de uma ética: bases conceituais sobre a ética da psicanálise no Seminário VII de Jacques Lacan - Freire, Rebecca Loise de Lucia (2015)
It refers to a theoretical research, based on freudian lacanian orientation, that intends to investigate which are the propositions and concepts used at the VII seminary to establish the ethics of psychoanalysis. First of all, we prepared a presentation about the ethics doubts made by Sigmund Freud, in a brief way of his work, based on the text which the author dedicates to discuss questions related to order, ethics and moral in psychoanalysis. As a part of Lacan s theory, we chose to make a deeply reading of his seminary, Book VII, The ethics of Psychoanalysis, showed in 1959 and 1960, in which he argued and discussed around the theme of ethics in psychoanalysis representing a fundamental tool that emphaticizes what Freud´s work and the analytic experience brought as new. For Lacan, the singularity of each individual is the most important item to think about; psychoanalytic ethics is exactly a singular ethics, because of neurotic´s myth being a construction based on a fictional order, tangled in its fundamental fantasy. As the main objective of this search, we want to answer the following questions: What does it mean to say that ethics in psychoanalysis are the unconscious desire s ethics? This question, because of its complexity size, imply in many theoretical unrolling. The specific main of this search refers to get deeper, in this way to visit Lacan s work in the VII seminary epoch, on how the analytic practice deals with the singular desire questions of the individual unconscious, relating to the following aspects: a) theoretical contexts & inquest of the clinical practice; b) the relationship between das Ding with the causation of desire; c) the confront between Kant and Sade and the access of the Thing d) the tragicomical dimention of the psychoanalytic experience